2004
DOI: 10.2355/isijinternational.44.809
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bottom Nozzle Configuration on the Bath Behaviour in the BOF

Abstract: Due to the different nature of the required measurements, two separate water models were utilised. Both models have the same geometry and dimensions; scaled down to 1 : 7. The operational and geometrical parameters of the physical model and the prototype are presented in Table 1. Figure 1 shows the location of bottom nozzles for 3, 4 and 5 nozzle arrangements. The two lance positions used in splashing and oscillation studies are also displayed in the same figure. Measurement of Splashing and SpittingSplashing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 35 publications
0
21
0
5
Order By: Relevance
“…The high mixing efficiency in the converter is largely attributed to stirring effects of the bottom injected gas. Therefore, the effects of various bottom nozzles conditions, [16][17][18][19]24,80,83) gas flow rates and gas supply schemes, 21,22,25,48,140) and combination schemed of top gas and bottom gas 20,26,27,30,78,79,119,141) are studied to optimize the mixing effects in the converter. The velocity distribution inside a 335-ton converter bath as well as the velocity and bubble size distribution in a six plugs 190-ton bottom blown converter with standard bottom stirring are presented in Fig.…”
Section: Stirring and Mixing Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The high mixing efficiency in the converter is largely attributed to stirring effects of the bottom injected gas. Therefore, the effects of various bottom nozzles conditions, [16][17][18][19]24,80,83) gas flow rates and gas supply schemes, 21,22,25,48,140) and combination schemed of top gas and bottom gas 20,26,27,30,78,79,119,141) are studied to optimize the mixing effects in the converter. The velocity distribution inside a 335-ton converter bath as well as the velocity and bubble size distribution in a six plugs 190-ton bottom blown converter with standard bottom stirring are presented in Fig.…”
Section: Stirring and Mixing Behaviormentioning
confidence: 99%
“…K. Nakanishi et al 9) investigated the mixing rate of molten steel and mass transfer rate between slag and metal in Q-BOP through water model experiments. Extensive studies were also carried out on the stirring behavior andbehavior mixing characteristics in top blown, [10][11][12][13][14][15] bottom blown, [16][17][18][19][20][21][22] as well as combined blown [23][24][25][26][27][28][29] converter at different stages 30) during a heat using water models. However, the transport phenomena in steel bath are so complex that many phenomena cannot be presented by water model experiments such as the compressibility of high speed oxygen, the interaction behavior between different phases, high temperature performance, etc.…”
mentioning
confidence: 99%
“…The latter peak most likely represents the frequency of the metallic bath standing wave caused by the impingement of the oxygen jet. 16,17) …”
Section: Vessel Vibration and Foam Heightmentioning
confidence: 99%
“…Their investigations indicated that better bath stirring could be obtained by increasing bottom nozzle eccentricity until a certain limit. Luomala et al 5) investigated the effect of three kinds of configurations of 3, 4 and 5 bottom nozzles on the bath behavior, such as splashing and spitting, bath homogenization and bath oscillation, respectively. Their results showed that configuration of three nozzles results the shortest mixing times when gas flow rate is low and pure bottom blowing results in shorter mixing times than combined blowing.…”
Section: Introductionmentioning
confidence: 99%